Engineering of new graphene-based materials as potential materials to assist near-infrared photothermal therapy cancer treatment. Issue 6 (June 2020) - Cheung, Faith
Abstract: Photothermal therapy is an emerging method of cancer treatment in which tumors are ablated by heating agents using near-infrared light (700–1000 nm). A semiconductor with a band gap between 0.3–0.7 eV would therefore efficiently emit near-infrared light. The new "magic" material graphene has a band gap of zero, which is advantageous with regard to designing a new material with a suitable band gap for the emission of near infrared light. In our investigations, using the first principles density functional theory calculation method, we aimed to and successfully designed graphene-based materials with a direct band gap of 0.68 eV. They have the potential to be optimal and efficient near-infrared light sources, due to their narrow yet fitting band gap. The present results open up a new avenue for the application of graphene-based materials to assist in photothermal therapy. Abstract : Biomedical engineering; Materials chemistry; Materials science; Oncology; Physical chemistry; Photothermal therapy; Band gap; Graphene; First principle calculation.